The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15279/kpba.2018.23.4.165
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hemorrhage from Gastroduodenal Artery Pseudoaneurysm following Endoscopic Ultrasound-Guided Fine Needle Aspiration of Pancreatic Head Mass

Abstract: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is a well-established procedure for the diagnosis of pancreatobiliary disease. Serious complications such as perforation, pancreatitis, hemorrhage, and sepsis are rarely reported. To our knowledge, delayed hemorrhage after EUS-FNA is very rare and hemorrhage from iatrogenic pseudoaneurysm has yet to be reported. We report a case of delayed hemorrhage from gastroduodenal artery pseudoaneurysm, which developed after EUS-FNA of a solid pancreatic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…TAE was performed for an inferior pancreaticoduodenal artery pseudoaneurysm; however, the patient died a few days later. Another study reported a case of bleeding complications ten days after EUS-FNA for a pancreatic head mass [ 6 ]. TAE was performed for a gastroduodenal artery branch pseudoaneurysm, and the bleeding was successfully controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAE was performed for an inferior pancreaticoduodenal artery pseudoaneurysm; however, the patient died a few days later. Another study reported a case of bleeding complications ten days after EUS-FNA for a pancreatic head mass [ 6 ]. TAE was performed for a gastroduodenal artery branch pseudoaneurysm, and the bleeding was successfully controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding is self-limiting in most cases, and endoscopic hemostasis and blood transfusions are rarely needed [ 4 ]. However, in a few cases of massive bleeding caused by EUS-FNA, transcatheter arterial embolization (TAE) has been reportedly used [ 5 , 6 ]. Here, we present a case series of six patients who underwent TAE for bleeding due to EUS-FNA.…”
Section: Introductionmentioning
confidence: 99%